Patient acceptance of AI-assisted diabetic retinopathy screening in primary care: findings from a questionnaire-based feasibility study - Krogh, Malene; Germund Nielsen, Marie; Byskov Petersen, Gabriela; Jensen, Morten Sig Ager; Jensen, Martin Bach; Vorum, Henrik; Bruun, Niels Henrik; Kolding Kristensen, Jette (Frontiers in Medicine, 2025)
AimThis feasibility study investigates patients' acceptance of AI-assisted diabetic retinopathy screening (DRS) in primary care.MethodPatients with type 2 diabetes from 12 primary care settings in Denmark underwent AI-assisted DRS as part of routine diabetes care and completed a questionnaire covering demographics, recent DRS, general health, mental well being, trust in physician, competence in diabetes self-care, distrust in AI, and acceptance of future DRS.Results298 patients participated and completed the questionnaire. Acceptance of future AI-assisted DRS in primary care was higher than that of ophthalmologist-led screening, although patients still showed distrust toward AI. Findings indicated that greater competence in diabetes self-care was associated with higher acceptance of future AI-assisted DRS in primary care. Lower distrust in AI increased acceptance of future AI-assisted DRS in primary care, while higher distrust increased acceptance of ophthalmologist-led DRS.ConclusionThis study found that most patients accepted future AI-assisted DRS in primary care. Associations between acceptance and the factors examined are very small and may have limited or no clinical impact. Other factors, such as convenience of having DRS in primary care, may influence patient's acceptance.